Modern Scots : an analytical survey - Millar, Robert McColl, 1966- (Edinburgh textbooks on the English language - advanced, 2018)
Your user-friendly study and revision guide to Scots criminal law, written specially for students by a law lecturer with over 20 years of teaching experience.